Biodiversity components and conservation of mediterranean healthlands in Southern Spain - Ojeda, F.; Arroyo, J.; MARAÑON, T. (Biological Conservation, 1995)
Biodiversity is a complex issue which has frequently been extremely simplified both by equating it with species richness, and by addressing it at the level of regional floras or faunas. In this paper we carry out a detailed assessment of biodiversity for conservation of Mediterranean heathlands and related woodland understoreys on acidic ‘islands’ in the Gibraltar Strait region which are remarkable for their high species richness, high endemism and low ratio of species per genus. The relationship between the cover of woody plant species and environmental variables was studied by multivariate (DCCA) analysis of 30 samples. Species richness shows a unimodal relationship along the main environmental gradient primarily determined by physiological tolerance to low pH and ecological competition. Quercus suber woodland understoreys under intermediate environmental conditions are highest in species richness. Woody plant species are assigned to one of seven types of geographic ranges, and distributional spectra of community samples are represented. Open heathlands on nutrient-poor soils on mountain ridges are highest in endemism. Species distinctness was estimated as the inverse of the average number of species per genus (‘taxonomic singularity’) within the Mediterranean Basin, Ibero-North African and Southwestern Spain ranges. Quercus canariensis woodland understoreys on more fertile soils on valley bottoms present the highest taxonomic singularity. The analysis at the community level of the three proposed biodiversity components (species richness, endemism richness and taxonomic singularity) is interpreted with the aim of formulating sound conservation strategies of the communities examined. Although we use communities in the Gibraltar Strait area as a particular case study, we suggest that this methodology would help conservation efforts in other areas.
Keywords: acid soils; endemism; Gibraltar Strait; historical biogeography; Species richness